WHISTLEBLOWING: PERAN TANGGUNG JAWAB PRIBADI, LOCUS OF CONTROL, DAN PROFESIONALISME - Harnold, Cut Shofira Maretti; Daud, Rulfah M.; Yulia, Aida; Ikhsan, Adhisyahfitri Evalina (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to explore the intricate dynamics surrounding whistleblowing within the context of personal responsibility, internal locus of control, and professionalism. The study focuses on auditors employed at the Aceh Provincial Inspectorate, involving an examination of 52 respondents. Non-probability sampling was employed using the method of Saturation Sampling (Census) due to the limited population size. Data collection for the study took place in August 2021, utilizing a questionnaire. Subsequently, data was analyzed using the Multiple Linear Regression method, facilitated by SPSS 22.0. The results show personal responsibility emerged as a significant factor influencing whistleblowing behaviors among auditors. The internal locus of control did not demonstrate an effect on whistleblowing. Professionalism exhibited an impact on whistleblowing. Moreover, personal responsibility, internal locus of control, and professionalism collectively affected whistleblowing. This research contributes valuable insights to the field by shedding light on the nuanced interplay of personal responsibility, internal locus of control, and professionalism in shaping whistleblowing tendencies among auditors at the Aceh Provincial Inspectorate.